Microsoft Office Access 2007 livelessons - Balter, Alison; Safari eBooks ([Indianapolis, Ind.] : Que, 2008)
"You've got Microsoft Office Access 2007... now get the most out of it, faster and more easily than ever before! In more than 80 quick video lessons, Alison Balter shows you all you need to maximize your productivity with Access 2007's best new tools and shortcuts and its brand-new ribbon interface! Microsoft Office Access 2007 teaches Access 2007's most sophisticated features and techniques visually: just watch! You'll master high-powered Office Access 2007 skills at your own pace--and get specific answers and solutions immediately, whenever you need them!"--Resource description page.
System requirements: Adobe Flash Player, version 8 or higher; or QuickTime Player, version 7.2 or higher; or Windows Media Player, version 11 or higher.
Title from resource description page (viewed March 9, 2009).
Electronic reproduction.
Keywords: Microsoft Access; Database management; Electronic books